Epidemiological methods in life course research - Pickles, Andrew; Maughan, Barbara, 1946-; Wadsworth, Michael E. J. (Michael Edwin John) (Oxford : Oxford University Press, 2007)
Life course epidemiology is concerned with how factors from the early development period, alongside genetic and environmental influences, can shape the future health of a person. This text explains the methods behind such research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Longitudinal studies; Life cycle, Human -- Health aspects; Lifestyles -- Health aspects; Life change events -- Health aspects